Trend Analysis of Admission, Enrollment and Completion in SNSU Gradu-ate Programs - Patulin, Elvis P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
For teachers, obtaining a bachelor's degree represents an important turning point in their academic careers and is unquestionably a positive step forward. Even while earning a bachelor's degree is an impressive accomplishment, it frequently is not enough to make the most impact on student's lives. Thus, upgrading themselves through enrollment in graduate programs equips them with an advanced technical understanding of their subject matter. The study focused on the trend analysis of admission, enrollment, and completion in the graduate programs of Surigao del Norte State University from SY 2010-2011 to SY 2021-2022. Data were taken from the Registrar's Office. At the same time, the factors contributing to the late and low completion rate in the programs were obtained purposively from sixty (60) respondents; most of them were graduate students who were identified to stop schooling in the semester where they were supposed to write their thesis and dissertation due to lack of funds needed to spend during the writing period of their research. The study revealed a growing trend in the admission, enrollment, and completion rates from SY 2010-2011 to SY 2021-2022. The growing trend is because adequate knowledge and skills can be obtained from enrolling in the graduate program, which could be primarily used in maximizing the teaching-learning process in the classroom by having the students as the recipient of learning. However, there is a low rate in terms of completion, which encouraged the author to recommend to the management to review the existing policies on writing research and improve its learning environment.